The role of money arguments in marriage - Britt, Sonya L.; Huston, Sandra J. (My University, 2012)
Despite the paucity of empirical evidence indicating the impact of money arguments on spousal relationship outcomes, it is common belief that money plays a large role in the life of couples. This study used panel data from the 1979 National Longitudinal Study of Youth (NLSY79) to examine how money-related arguments affect the marital relationship. Economic theory indicates that initial expectations about the marriage and variance in expectations are both important in predicting relationship satisfaction and divorce. Money arguments were modeled as a sign of the lack of investment in spousal-specific capital and were hypothesized to negatively impact relationship quality. Results suggest that money arguments are an important indicator of relationship satisfaction, but are not as influential in predicting divorce. Both the approach used to model money arguments and the empirical results can be used by marriage therapists and financial counselors to help couples understand and improve the benefits received through marriage.
Keywords: Money arguments; Divorce; Relationship satisfaction; Predictors